Swedish analogy test set v1.0 - Språkbanken Text (University of Gothenburg, 2024)
Swedish semantic and syntactic similarity: test set

Svensk semantisk och syntaktisk likhet: testmängd
Svensk analogi testmängd v1.0
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik